Peran pendidikan pandu dalam meningkatkan kepemimpinan peserta didik di Sekolah Pemimpin MA Hidayatullah Depok - Lathiefah, Sayyidah Laila; Priatna, Oking Setia; Tanjung, Hasan Basri (Tawazun: Jurnal Pendidikan Islam, 2022)
This study aims to determine the role of Scout Education in Improving Student Leadership at the Leader School of MA Hidayatullah Depok. This research is a qualitative research with data collection techniques in the form of observation studies, interviews and documentation. The results of this study reveal several important things: First, the implementation of scout education at the Leader School of MA Hidayatullah Depok is carried out like scouts in general, only the difference is that it combines two curricula, namely the national (kemenag) curriculum with an integral curriculum based on monotheism. Second, the leadership of the students at the Leader School of MA Hidayatullah Depok is good, this can be seen from the skills in mobilizing other students and the responsibility for the mandate given. Third, the role of scout education in improving the leadership of students at the Leader School of MA Hidayatullah Depok, among others, namely being trustworthy towards the assigned tasks, skilled in communication, brave in making decisions, having a straight aqidah, increasing intellectual and spiritual intelligence, being honest, initiative and able to work together with other people. Abstrak Penelitian ini bertujuan untuk mengetahui Peran Pendidikan Pandu dalam Meningkatkan Kepemimpinan Peserta didik di Sekolah Pemimpin MA Hidayatullah Depok. Penelitian ini merupakan penelitian kualitatif dengan teknik pengumpulan data berupa studi observasi, wawancara dan dokumentasi. Hasil penelitian ini mengungkapkan beberapa hal penting: Pertama, pelaksanaan pendidikan pandu di Sekolah Pemimpin MA Hidayatullah Depok dilaksanakan seperti pramuka pada umumnya, hanya saja yang membedakan ialah mengombinasikan dua kurikulum, yaitu kurikulum nasional (Kemenag) dengan kurikulum integral berbasis tauhid. Kedua, kepemimpinan peserta didik di Sekolah Pemimpin MA Hidayatullah Depok sudah baik, hal tersebut terlihat dari kecakapan dalam menggerakkan peserta didik yang lain dan tanggung jawab terhadap amanah yang diberikan. Ketiga, peran pendidikan pandu dalam meningkatkan kepemimpinan peserta didik di Sekolah Pemimpin MA Hidayatullah Depok di antaranya yaitu amanah terhadap tugas yang diberikan, terampil dalam berkomunikasi, berani dalam mengambil keputusan, memiliki aqidah yang lurus, meningkatkan kecerdasan intelektual dan spiritual, jujur, inisiatif dan mampu bekerjasama dengan orang lain.